Pelatihan Aplikasi Toko Online Di SMA Ciledug Tangerang - Arsanto Narendro; Wisjhnuadji (AMMA : Jurnal Pengabdian Masyarakat, 2023)
In order to increase the insight of the teachers and employees of Ciledug Tangerang High School, one way is to equip them with knowledge and skills in utilizing computer technology, especially in the field of applications to improve family economic capabilities by making buying and selling transactions online. Several web and mobile-based platforms have been widely circulated and are in great demand by the public, especially for those who will do business online, such as OLX, Tokopedia, Bukalapak, Shopee and many others. By going directly and using the application, you will get many benefits, including transactions that can be done from anywhere, especially from your home or office, so this will save time and money. Meanwhile, the main activity as an office or company employee does not have to be disturbed because along with this online transaction activity. By providing training on how to use online applications for transactions, whether selling or buying something, it is hoped that it can help the family economy, especially teachers and employees.